Biogeographic notes on rare species of Euglossina (Hymenoptera: Apidae: Apini) occurring in the Brazilian Atlantic Rain Forest - Nemésio,André (2004)
The significance of specimens of rare species of Euglossina collected recently is discussed in terms of elucidating their biogeography and conservation status. Particularly, two new records are presented for the state of Minas Gerais, which considerably increase the known geographic range of the species they represent. These are a male of Eufriesea aeneiventris (Mocsáry), last recorded in 1943, which was attracted to methyl salicylate at the Parque Estadual do Rio Doce, and a male of Eulaema seabrai collected on flowers in the urban area of Sabará. This is also the first record for this species in the state.